2018
DOI: 10.1007/s13224-018-1153-1
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Blues: Why Do Research Papers Get Rejected?

Abstract: It is really disheartening when your paper gets rejected by a journal. Authors work very hard to conduct research. They present their work in the form of platform presentation in a conference and/or as a research article for publication. When their platform presentations get applauded by the audience, researchers feel encouraged to publish it. However, it may not be appreciated by editors and reviewers when the research is submitted to a journal for publication. One should not get disappointed by rejections. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 3 publications
0
23
0
2
Order By: Relevance
“…It is not uncommon, and any author should be completely aware of this reality. Some journals report rejection rates of as high as 90-95%, but don't lose hope (Khadilkar 2018), depending on the details of the work it can often be resubmitted elsewhere, in fact it is reported that 62% of articles accepted have been rejected elsewhere (Khadilkar 2018). It is good practice to aim high and have several suitable journals in mind for each article.…”
Section: Tipmentioning
confidence: 99%
“…It is not uncommon, and any author should be completely aware of this reality. Some journals report rejection rates of as high as 90-95%, but don't lose hope (Khadilkar 2018), depending on the details of the work it can often be resubmitted elsewhere, in fact it is reported that 62% of articles accepted have been rejected elsewhere (Khadilkar 2018). It is good practice to aim high and have several suitable journals in mind for each article.…”
Section: Tipmentioning
confidence: 99%
“…The submission of auxiliary documents that are necessary (ethics, conflict of interest) may have not been sent. The Editor in charge first looks at the title and the topic of the research [1,2]. When he feels that it may not have much interest to his readers, the paper can be directly sent back at this level.…”
Section: What Are Reasons For the Outright Rejection Of A Manuscript?mentioning
confidence: 99%
“…Quando suas apresentações são aplaudidas pelo público, pesquisadores sentem-se incentivados a publicar seus artigos. No entanto, seus trabalhos, por diferentes motivos, podem acabar não sendo priorizados pelos editores e revisores quando a pesquisa é submetida a uma revista (Khadilkar, 2018).…”
Section: Lições Que Podem Ser Aprendidas Da Rejeição De Um Artigounclassified